The Incidence of Chromosomal Aberrations in Prenatally Diagnosed Isolated Agenesis of the Corpus Callosum - Rüland, Anna Marlene; Gloning, Karl-Philipp; Albig, Matthias; Kagan, Karl-Oliver; Hammer, Rüdiger; Schälike, Michael; Berg, Christoph; Gembruch, Ulrich; Geipel, Annegret (Ultraschall in der Medizin - European Journal of Ultrasound, 2017)
Purpose To establish the prevalence of chromosomal aberrations in fetuses with an apparently isolated agenesis of the corpus callosum (ACC) on prenatal ultrasound.Materials & Methods This was a retrospective study of complete isolated ACC at the time of ultrasound evaluation with respect to karyotype information. Within this group, a subgroup with non-malformation minor abnormalities, such as a single umbilical artery (SUA), polyhydramnios or fetal growth restriction (FGR), was investigated.Results Complete ACC was diagnosed in 343 cases. Of them, 143 (41.6 %) were isolated, with 16 fetuses showing additional minor findings. In 76.2 % (109/143) karyotyping was performed. Additional array CGH analysis was performed in 7.7 % (11/143). Chromosomal aberrations were found in 4.6 % (5/109) overall, in 3.1 % (3/98) of those without any additional sonographic findings (all represented mosaic trisomy 8) and in 18.2 % (2/11) of those with minor abnormalities. The prevalence of pathogenic submicroscopic copy number variant (CNV) was 9 % (1/11).Conclusion Fetal karyotyping is recommended in ACC, as trisomy 8 mosaicism should be considered despite otherwise unremarkable ultrasound. The role of novel techniques such as array CGH and its implication has to be explored in prospective studies.
Keywords: corpus callosum agenesis; prenatal diagnosis; ultrasonography; karyotype; prenatal Array CGH